Consumption of sugar sweetened beverages, artificially sweetened beverages and fruit juices and risk of type 2 diabetes, hypertension, cardiovascular disease, and mortality: A meta-analysis - Li, Baoyu; Yan, Ni; Jiang, Hong; Cui, Meng; Wu, Min; Wang, Lina; Mi, Baibing; Li, Zhaofang; Shi, Jia; Fan, Yahui; Azalati, Mougni Mohamed; Li, Chao; et al. (Frontiers in Nutrition, 2023)
Sugar-sweetened beverage (SSB) intake is associated with an increased risk of cardiometabolic diseases. However, evidence regarding associations of artificially sweetened beverages (ASBs) and fruit juices with cardiometabolic diseases is mixed. In this study, we aimed to investigate the association between the SSB, ASB and fruit juice consumption with the incidence of cardiometabolic conditions and mortality. Relevant prospective studies were identified by searching PubMed, Web of Science, Embase, and Cochrane Library until December 2022 without language restrictions. The pooled relative risk (RR) and 95% confidence intervals (CIs) were estimated for the association of SSBs, ASBs, and fruit juices with the risk of type 2 diabetes (T2D), cardiovascular disease (CVD), and mortality by using random-effect models. A total of 72 articles were included in this meta-analysis study. Significantly positive associations were observed between the consumption of individual beverages and T2D risk (RR: 1.27; 95% CI: 1.17, 1.38 for SSBs; RR: 1.32; 95% CI: 1.11, 1.56 for ASBs; and RR:0.98; 95% CI: 0.93, 1.03 for fruit juices). Moreover, our findings showed that intakes of SSBs and ASBs were significantly associated with risk of hypertension, stroke, and all-cause mortality (RR ranging from 1.08 to 1.54; all P<0.05). A dose-response meta-analysis showed monotonic associations between SSB intake and hypertension, T2D, coronary heart disease (CHD), stroke and mortality, and the linear association was only significant between ASB consumption and hypertension risk. Higher SSB and ASB consumptions were associated with a greater risk of developing cardiometabolic diseases and mortality. Fruit juice intake was associated with a higher risk of T2D. Therefore, our findings suggest that neither ASBs nor fruit juices could be considered as healthier beverages alternative to SSBs for achieving improved health.